1999
DOI: 10.1111/j.1528-1157.1999.tb00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cognitive Effects of Carbamazepine and Gabapentin

Abstract: Summary:Purpose: The cognitive effects of the newer antiepileptic drugs (AEDs) compared with the older standard AEDs are uncertain.Methods: We directly compared the cognitive effects of carbamazepine (CBZ) and gabapentin (GBP) in 35 healthy subjects by using a double-blind, randomized crossover design with two 5-week treatment periods. During each treatment condition, subjects received either GBP, 2,400 mg/day, or CBZ (mean, 731 mg/day) adjusted to a dose to achieve midrange standard therapeutic blood levels (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
2
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(68 citation statements)
references
References 23 publications
4
56
2
6
Order By: Relevance
“…Reviewing the literature, it seems that TGB, similar to GABA A -or benzodiazepinereceptor agonists, evokes the impairment of acquisition and, additionallyFin contrast to these agonists, impairs the retrieval of the task. On the other hand, in patients with epilepsy, TGB and other GABA enhancers, such as GBP or VGB improved memory and cognitive functions (Kalviainen, 1998;Kalviainen et al, 1995;Mortimore et al, 1998;Meador et al, 1999). So far, considering the results of our study, as well as available evidence, it is difficult, at present, to unequivocally ascertain whether or not TGB disturbs the memory in animals.…”
Section: Controlcontrasting
confidence: 47%
“…Reviewing the literature, it seems that TGB, similar to GABA A -or benzodiazepinereceptor agonists, evokes the impairment of acquisition and, additionallyFin contrast to these agonists, impairs the retrieval of the task. On the other hand, in patients with epilepsy, TGB and other GABA enhancers, such as GBP or VGB improved memory and cognitive functions (Kalviainen, 1998;Kalviainen et al, 1995;Mortimore et al, 1998;Meador et al, 1999). So far, considering the results of our study, as well as available evidence, it is difficult, at present, to unequivocally ascertain whether or not TGB disturbs the memory in animals.…”
Section: Controlcontrasting
confidence: 47%
“…Considering cognitive functioning, we found that these relatively well-controlled patients performed significantly worse on memory, selective and divided attention functions, and speed of information processing than the matched healthy controls. The diminished speed of information processing we found has also been established by pharmacological studies and might be due to medication [32]. REM sleep deprivation for example, caused by CBZ, might have affected cognitive performance, although the magnitude of this effect compared with other epilepsy-related characteristics remains controversial [33].…”
Section: Discussionmentioning
confidence: 93%
“…Most studies tend to report little or no cognitive impairment in association with gabapentin, including double-blind studies [Dodrill et al 1999;Meador et al 1999;Leach et al 1997], and there may be potential for improved performance in cognitive measures [Mortimore et al 1998]. …”
Section: Gabapentinmentioning
confidence: 99%